2019
DOI: 10.3390/cancers11030411
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Macropinocytosis Processes in Glioblastomas May Be Exploited to Increase Intracellular Anti-Cancer Drug Levels: The Example of Temozolomide

Abstract: Macropinocytosis is a clathrin-independent endocytosis of extracellular fluid that may contribute to cancer aggressiveness through nutrient supply, recycling of plasma membrane and receptors, and exosome internalization. Macropinocytosis may be notably triggered by epidermal growth factor receptor (EGFR) and platelet-derived growth factor receptor (PDGFR), two well-known markers for glioblastoma aggressiveness. Therefore, we studied whether the expression of key actors of macropinocytosis is modified in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 92 publications
(175 reference statements)
0
22
0
Order By: Relevance
“…Moreover, we showed that the ability of CX-4945 to promote methuotic cell death was cell type-specific since the extent of the vacuolization that followed CX-4945 stimulation considerably differed amongst the various cell lines used, distinguishing highly sensitive cells (i.e., HepG2 and GN11), moderately sensitive cells (i.e., MDA-MB-231 and HEK-293 T) and insensitive cells (i.e., HeLa). Although the concept of off-target effects has a negative connotation, the finding that CX-4945 promotes this non-canonical mechanism of cell death could represent an added value, rather than an obstacle, in the context of anti-cancer combination therapy for at least two reasons: 1) induction of methuosis could represent a feasible anti-tumour approach for those tumours that acquired the ability to escape from apoptosis or that developed resistance to classical apoptosis inducing agents; 2) enhancing macro-pinocytosis, CX-4945 could favour the uptake of additional drugs, thus representing an ideal condition for a pharmacological therapy that involves the use of multiple drugs, as shown in [41], where doxorubicin accumulation in tumour cells was greatly increased by CX-4945 co-administration, or as suggested by Colin et al co-treating GBM cells with temozolomide and different methuotic-inducing compounds [96]. This latter effect would greatly favour a combination therapy, but future work will be necessary to exactly understand the effective contribution of methuosis induction in different types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we showed that the ability of CX-4945 to promote methuotic cell death was cell type-specific since the extent of the vacuolization that followed CX-4945 stimulation considerably differed amongst the various cell lines used, distinguishing highly sensitive cells (i.e., HepG2 and GN11), moderately sensitive cells (i.e., MDA-MB-231 and HEK-293 T) and insensitive cells (i.e., HeLa). Although the concept of off-target effects has a negative connotation, the finding that CX-4945 promotes this non-canonical mechanism of cell death could represent an added value, rather than an obstacle, in the context of anti-cancer combination therapy for at least two reasons: 1) induction of methuosis could represent a feasible anti-tumour approach for those tumours that acquired the ability to escape from apoptosis or that developed resistance to classical apoptosis inducing agents; 2) enhancing macro-pinocytosis, CX-4945 could favour the uptake of additional drugs, thus representing an ideal condition for a pharmacological therapy that involves the use of multiple drugs, as shown in [41], where doxorubicin accumulation in tumour cells was greatly increased by CX-4945 co-administration, or as suggested by Colin et al co-treating GBM cells with temozolomide and different methuotic-inducing compounds [96]. This latter effect would greatly favour a combination therapy, but future work will be necessary to exactly understand the effective contribution of methuosis induction in different types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…By treating NSCLC, neuroblastoma, glioblastoma and melanoma cell lines with increasing concentrations of fluorescently-labelled recombinant Omomyc, we observed that Omomyc penetrated cells in a dose-dependent fashion, mainly through clathrin-mediated endocytosis and macropinocytosis (in addition to some caveolin-dependent mechanism), with a significant proportion of the protein localized in the nuclei [79]. Notably, macropinocytosis is a particularly interesting endocytosis mechanism for cancer treatment, since it is enhanced in cancer cells compared to normal cells and therefore could favor the targeting of Omomyc to tumor cells [80]. The mechanism of entry of Omomyc is highly dependent on its basic region, since an Omomyc mutant with reduced arginine content in this region is unable to penetrate cells [79].…”
Section: Recombinant Omomyc Is a Cell-penetrating Peptidementioning
confidence: 95%
“…Moreover, macropinocytosis does not specifically target molecules in the extracellular environment, indicating that EV uptake may be dictated just by their proximity to the cell membrane. Nevertheless, macropinocytosis is regulated by specific mechanisms ( Bryant et al, 2007 ; Ha et al, 2016 ; Colin et al, 2019 ); stimulation, e.g., of the epidermal growth factor receptor, enhances EV uptake ( Nakase et al, 2015 ; Colin et al, 2019 ). Notably, also EVs appear to induce macropinocytosis ( Costa Verdera et al, 2017 ).…”
Section: “Eating and Drinking” Evsmentioning
confidence: 99%